2016
DOI: 10.1002/jclp.22268
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility and Predictive Validity of Parent and College Student Symptom Ratings in Predicting an ADHD Diagnosis

Abstract: These results fill an important gap in the literature. Overall, results suggest that rating scales can be used effectively to evaluate ADHD on college campuses as long as both parent and student ratings of childhood symptoms are collected. Importantly, collecting parent ratings protects against possible student malingering to obtain ADHD medications or accommodations. Additional research with larger samples and across multiple universities is needed to establish best practices in the diagnosis of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…There are only moderate correlations between self and informant reports on ADHD behavior rating scales (Barkley, Knouse, & Murphy, 2011;Van Voorhees, Hardy, Kollins, 2011, Zucker, Morris, Ingram, Morris, & Bakeman, 2002. Dvorsky, Langberg, Molitor, and Bourchtein (2016) found parent ratings were superior to those of college students in predicting the latter's ADHD diagnosis. On the other hand, based on their substantial clinical experience, Murphy and Gordon (2006) have opined that the patient is a more reliable reporter than an informant.…”
Section: Diagnostic Issuesmentioning
confidence: 78%
See 1 more Smart Citation
“…There are only moderate correlations between self and informant reports on ADHD behavior rating scales (Barkley, Knouse, & Murphy, 2011;Van Voorhees, Hardy, Kollins, 2011, Zucker, Morris, Ingram, Morris, & Bakeman, 2002. Dvorsky, Langberg, Molitor, and Bourchtein (2016) found parent ratings were superior to those of college students in predicting the latter's ADHD diagnosis. On the other hand, based on their substantial clinical experience, Murphy and Gordon (2006) have opined that the patient is a more reliable reporter than an informant.…”
Section: Diagnostic Issuesmentioning
confidence: 78%
“…In college populations, Dvorsky et al (2016) reported the sensitivity and specificity of the BAARS-IV self-report current inattention symptoms ratings were 89% and 30% respectively while those for the self-report childhood inattention symptom ratings were 65% and 40% respectively. On the other hand, Harrison, Nay, and Armstrong (2019) found the current CAARS ADHD Index score (Conners Adult ADHD Rating Scales, Conners, Erhardt, & Sparrow, 1999) (t score ¼ 65) had a sensitivity of 64% and specificity of 86% in a postsecondary population.…”
Section: Diagnostic Accuracymentioning
confidence: 97%
“…In the present study, we did not collect corroborating information from collateral reports. Because of the somewhat conflicting results of self-reports, collateral reports are often recommended for adult ADHD diagnosis 20. However, besides the difficulty in obtaining informant reports for this population (adult ADHD diagnosis without collateral reports abound in the literature, unlike child or adolescent ADHD), many factors influence significant others’ or relatives’ ratings on behavioral questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…In Dr. Nelson's university-based clinic, third-party informants were readily available for 97% of clients over the past year. Recent research (e.g., Dvorsky et al, 2016) has found informant reports of ADHD symptoms to be even more accurate than selfreports, and every effort should be made to obtain information from at least one third-party informant (preferably more).…”
Section: The Initial Referral Meetingmentioning
confidence: 99%